2016
DOI: 10.1007/s11104-016-3031-x
|View full text |Cite
|
Sign up to set email alerts
|

Do organic inputs matter – a meta-analysis of additional yield effects for arable crops in Europe

Abstract: Background and aims Organic inputs have a positive effect on the soil organic matter balance. They are therefore an important asset for soil fertility and crop growth. This study quantifies the additional yield effect due to organic inputs for arable crops in Europe when macronutrients are not a limiting factor. Methods A meta-analysis was performed using data from 20 long-term experiments in Europe. Maxima of yield response curves to nitrogen were compared, with and without organic inputs, under abundant P an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
144
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(158 citation statements)
references
References 52 publications
(30 reference statements)
10
144
1
3
Order By: Relevance
“…4). This observation agrees with the study of Hijbeek et al (2017), who found that maize benefits significantly from organic inputs than those of wheat or barley. The most likely reason for this difference was that, compared to wheat, maize is mostly grown 10 require with higher temperature and precipitation (Tan et al, 2017), and these conditions favor a fasten straw decomposition and also result in a more rapid and abundant nutrient release (Hartmann et al, 2014;Ladha et al, 2011).…”
supporting
confidence: 93%
“…4). This observation agrees with the study of Hijbeek et al (2017), who found that maize benefits significantly from organic inputs than those of wheat or barley. The most likely reason for this difference was that, compared to wheat, maize is mostly grown 10 require with higher temperature and precipitation (Tan et al, 2017), and these conditions favor a fasten straw decomposition and also result in a more rapid and abundant nutrient release (Hartmann et al, 2014;Ladha et al, 2011).…”
supporting
confidence: 93%
“…The effects of crop residue incorporation on soil chemical, physical and biological quality were mainly positive, and agree with the previous literature (Hijbeek et al . (). As reported in Lehtinen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Hijbeek et al . () selected 20 LTEs, of which some were from the same database, to investigate the additional value of organic amendments when macronutrients were applied in sufficient amounts. They found a significant correlation between increases in soil organic matter contents and increases in crop yields; however, the mean additional yield effect of organic amendments remained insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…In the sandy loam at Woburn, modelling with RothC‐26.3, showed that 5%, at most, of the C added in plant residues over a 70‐year period is still present in the soil (Johnston et al., ) but, again, this caused measurable changes in soil properties. However, improvements in soil physical properties caused by increased SOC do not necessarily translate into consistently increased crop yields (Hijbeek et al., ).…”
Section: Discussionmentioning
confidence: 99%